STUCTURAL EQUATION MODELING-PARTIAL LEAST SQUARE-UNTUK PERMODELAN PENGARUH KOMPETENSI KEWIRAUSAHAAN TERHADAP KINERJA USAHA KEDAI KOPI SKALA KECIL DI KOTA PADANG - Paloma, Cindy; Yusmarni, Yusmarni; Putri, Afrianingsih; Hasnah, Hasnah (Jurnal AGRISEP, 2022)
During the COVID-19 pandemic, the growth of small-scale coffee shops has increased in Padang city. This condition indicates the high level of coffee consumption and the increased competition of coffee shops. A good entrepreneurship competency is needed to improve business performance. This research aims to analyze the influence of entrepreneurial competency on small-scale coffee shop business performance in Padang City. This research used an Entrepreneurial competency model influenced by psychological characteristics (indicated by motivation, achievement, socialize need) and environmental factors (characterized by social net, government policy, and supply). The business performance model is influenced by entrepreneurial competency (managerial skill, conceptual skill, social skill, decision-making skill, and time managerial skill)  and environmental factors. This research used a snowball sampling method of 100 data samples of small-scale coffee shops (owner and barista) in Padang City from April until May 2021. The data was then analyzed by SEM-PLS analysis with SMART PLS 3.3 software. The result showed that psychological characteristics and environmental factors influenced the entrepreneurial competency in small-scale coffee shops. The business performance was influenced by entrepreneurial competency and environmental factors in the small-scale model. The results also show that the model was used in this research has a Model Fit of 84%.